2005
DOI: 10.1007/s10592-005-4974-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene associated tandem repeat markers in Atlantic salmon (Salmo salar L.) populations: implications for restoration and conservation in the Baltic Sea

Abstract: Patterns of genetic diversity and differentiation among five wild and four hatchery populations of Atlantic salmon in the Baltic Sea were assessed based on eight assumedly neutral microsatellite loci and six geneassociated markers, including four expressed sequence tag (EST) linked and two major histocompatibility complex (MHC) linked tandem repeat markers (micro-and mini-satellites). The coalescent simulations based on the method of Beaumont and Nichols (1996, Proc. R. Soc. Lond. Ser. B -Biol. Sci., 263, 1619… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Therefore, further studies are warranted in order to determine the true homology of this gene sequence in salmon and whether the effects of selection might have implications for its use as a reference gene in expression studies. Interestingly, the MHC II beta locus, which was selected as an a priori candidate for selection, did not deviate from the simulated neutral expectations (Figure 8), despite the fact that the locus has been identified as an outlier in several population genetic studies of Atlantic salmon (Landry and Bernatchez 2001;Vasemägi, Gross, et al 2005) and has also been demonstrated to directly affect the survival in several disease trials (Langefors et al 2001;Lohm et al 2002) and during empirical experiments in natural environment (de Eyto et al 2007). To conclude, the main limitation on the use of biallelic markers in ecology and population genetics of nonmodel species continues to be the lack of markers, and this, together with the low information content compared with microsatellites (Kalinowski 2002), hinders their application in nonmodel organisms.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, further studies are warranted in order to determine the true homology of this gene sequence in salmon and whether the effects of selection might have implications for its use as a reference gene in expression studies. Interestingly, the MHC II beta locus, which was selected as an a priori candidate for selection, did not deviate from the simulated neutral expectations (Figure 8), despite the fact that the locus has been identified as an outlier in several population genetic studies of Atlantic salmon (Landry and Bernatchez 2001;Vasemägi, Gross, et al 2005) and has also been demonstrated to directly affect the survival in several disease trials (Langefors et al 2001;Lohm et al 2002) and during empirical experiments in natural environment (de Eyto et al 2007). To conclude, the main limitation on the use of biallelic markers in ecology and population genetics of nonmodel species continues to be the lack of markers, and this, together with the low information content compared with microsatellites (Kalinowski 2002), hinders their application in nonmodel organisms.…”
Section: Discussionmentioning
confidence: 88%
“…This method builds the expected neutral distribution of F ST as a function of heterozygosity, based on coalescent simulations, to which the observed distribution of F ST at Adaptive genetic variation in brown trout LF Jensen et al individual loci can be compared. Beaumont and Nichols (1996) showed that this procedure is rather robust to many violations in assumptions used to generate the expected distribution, for example model of population structure and mutation rate, and the approach has been applied to detect selection in several studies (Storz and Dubach, 2004;Vasemägi et al, 2005;Aguilar and Garza, 2006). Specifically, all simulations were based on 50 000 realizations assuming a stepwise mutation model.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Grayling exhibit very low overall genetic diversity (Koskinen et al 2002c;Susnik et al 2004;Gum et al 2006) compared to other salmonids (e.g. Vasemägi et al 2005;Gross et al 2007;Fave and Turgeon 2008;Lehtonen et al 2009). The population structure of grayling has been recently characterized throughout Finland and three previously unanticipated population groups have been described, corresponding to the northern, Baltic and southeastern geographic regions (Swatdipong et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…An increasing number of studies have detected such bottleneck footprints in various species groups, including insects (Dhuyvetter et al 2005;Chen et al 2006), mollusks (Bouza et al 2007), amphibians (Beebee and Rowe 2001), reptiles (Russello et al 2007), birds (Lambert et al 2005), fish (Vasemägi et al 2005;Vähä et al 2007) and mammals (Lucchini et al 2004;Fernandez-Stolz et al 2007). However, it has been shown that bottlenecks generate detectable genetic footprints only in extreme cases when effective population sizes decreases rapidly to tens rather than to hundreds of individuals (Luikart and Cornuet 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation